Authorship associated misconduct - a rising problem in Nepalese medical academia - Chaulagain, Rajib; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2021)
A medical practitioner or researcher’s contribution is judged not only on the basis of number of patients treated or the years of practice, but also, through publications. It is through your publications, your work is validated and the lifelong techniques is disseminated to your juniors, fellows, residents and even to your colleagues. Publishing also is a source for academic development and a means to enrich yourself by critically reviewing others works. In addition, your publication provides the research-gap for future researchers to conduct additional studies. In many countries including Nepal, publication is also a basis of promotion in academics. So, research,scientific writing and publishing is a part of medical and dental academia